2016
DOI: 10.3109/10826084.2016.1155613
|View full text |Cite
|
Sign up to set email alerts
|

College Student Dating Partner Drinking Profiles: Differences in Relationship Functioning and Relationship-Specific Alcohol Expectancies

Abstract: Background Although the majority of research on partner drinking styles has examined married couples, dating partners may influence one another's problem behaviors including alcohol use. Objectives This study identified patterns of at-risk alcohol use in college women and their dating partners using a person-centered statistical approach (i.e., latent profile analysis). Methods Participants were 286 college student women in dating relationships. They completed questionnaires regarding their own and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Given previous research on the importance of alcohol consumption in romantic relationships, 11,[13][14][15] the present study sought to investigate similarity of both drinking behavior and drinking motivations in romantic couples. Results suggested that couples are more similar in their drinking behavior profiles than expected by chance, consistent with prior research on alcohol consumption similarity in couples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given previous research on the importance of alcohol consumption in romantic relationships, 11,[13][14][15] the present study sought to investigate similarity of both drinking behavior and drinking motivations in romantic couples. Results suggested that couples are more similar in their drinking behavior profiles than expected by chance, consistent with prior research on alcohol consumption similarity in couples.…”
Section: Discussionmentioning
confidence: 99%
“…As evidence of this, romantic partners influence each others’ heavy episodic drinking over periods up to 3 years, suggesting that heavy drinking should be considered a couples’ issue instead of just an individual issue. 12 Drinking partnerships have also been associated with relationship satisfaction, with heavy drinking couples typically reporting less satisfaction 13 and increased intimate partner violence. 14 Moreover, discrepancy in drinking within couples is associated with more alcohol-related problems and consequences over time 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While rates of violence vary, DV has been consistently associated with increased alcohol use among college students (Dardis et al, 2015;Shorey et al, 2011), with alcohol use linked to partner violence (Devries et al, 2014;Shorey et al, 2011). Furthermore, violence among dating couples has been associated with high-risk drinking (Linden-Carmichael et al, 2016). These studies have informed intervention efforts to decrease alcohol use (see review by Samson & Tanner-Smith, 2015) and to increase bystander interventions to reduce DV on college campuses (Coker et al, 2015;Fleming, Wiersma-Mosley, 2015).…”
Section: And Alcohol Use Among College Studentsmentioning
confidence: 99%
“…Congruence of drinking patterns between partners is associated with relationship satisfaction (Homish & Leonard, 2007). Thus, drinking partnerships may sometimes be beneficial to relationship functioning (e.g., Linden-Carmichael, Lau-Barraco, & Kelley, 2016).…”
Section: Partner Influence and Alcohol Consumptionmentioning
confidence: 99%